A surfactant for industrial wastewater and preparation method thereof

By preparing a surfactant for industrial wastewater containing polyacrylamide, kaolin, activated carbon, lignin/Ni-MOF composite gel, composite photocatalyst and modified polyacrylic acid, the problem of poor treatment effect of difficult degradation of organic pollutants in industrial wastewater is solved, and efficient wastewater purification is achieved.

CN119118329BActive Publication Date: 2025-04-18CHONGQING MINDONG CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411417473.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-04-18
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Industrial wastewater contains difficult-to-degrade organic pollutants, and the existing treatment methods are limited in effect, making it difficult to effectively remove these pollutants.

Method used

A surfactant for industrial wastewater is prepared, including polyacrylamide, kaolin, activated carbon, lignin/Ni-MOF composite gel, composite photocatalyst and modified polyacrylic acid. Through the combination of these components, efficient adsorption, flocculation and photoinduced degradation of pollutants in wastewater are achieved.

Benefits of technology

The purification efficiency of wastewater is significantly improved. The lignin/Ni-MOF composite gel has excellent adsorption and flocculation properties. The modified polyacrylic acid is purified by electrostatic adsorption and chelation, and the composite photocatalyst further improves the purification effect through photo-induced degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079837960000101
    Figure BDA0005079837960000101
  • Figure BDA0005079837960000111
    Figure BDA0005079837960000111
Patent Text Reader

Abstract

The present invention relates to the technical field of wastewater treatment, and discloses a surfactant for industrial wastewater and a preparation method thereof. The surfactant prepared by the present invention is a composition, which is formed by stirring and mixing polyacrylamide, kaolin, activated carbon, lignin / Ni-MOF composite gel, composite photocatalyst and modified polyacrylic acid, and when applied to the purification of industrial wastewater, the purification efficiency of wastewater can be significantly improved; wherein, the lignin / Ni-MOF composite gel has excellent adsorption, flocculation and recyclability; the modified polyacrylic acid achieves the purpose of purification through electrostatic adsorption or chelation; the composite photocatalyst further improves the purification of wastewater by photocatalytic degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a surfactant for industrial wastewater and a preparation method thereof. Background Art

[0002] Industrial wastewater mainly refers to wastewater and waste liquid generated during industrial production, which contain pollutants such as lost raw materials, intermediates and by-products used in industrial production. At present, with the rapid development of coking, printing and dyeing, papermaking, pesticides, medicine, petrochemicals and other industries, the types and quantities of industrial wastewater containing difficult-to-degrade organic pollutants are increasing. The main pollutants are organic cyanides, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), dyes, antibiotics and other organic substances with stable structures and difficult biodegradation. These pollutants can cause many hazards, such as harm to aquatic organisms and the water environment, toxic effects on the human body, and harm to crops. Therefore, it is necessary to treat industrial wastewater to effectively remove organic and inorganic pollutants in the wastewater so as to meet the requirements of effluent water quality.

[0003] Traditional methods for treating industrial wastewater mainly include: adsorption method, membrane separation technology, oxidation pond method, bio-augmentation technology, flocculation sedimentation method, advanced oxidation technology, etc. However, the effect achieved by a single treatment method is limited. Therefore, it is necessary to combine several methods, such as: combining adsorption method and flocculation sedimentation method to prepare a surfactant with the advantages of high adsorption performance and excellent flocculation effect, so as to improve the wastewater treatment effect. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a surfactant for industrial wastewater and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A surfactant for industrial wastewater, comprising the following raw materials in parts by weight: 20-30 parts of polyacrylamide, 7-10 parts of kaolin, 3-6 parts of activated carbon, 5-12 parts of lignin / Ni-MOF composite gel, 3-6 parts of composite photocatalyst, and 3-5 parts of modified polyacrylic acid;

[0007] The composite photocatalyst is formed by mixing nano zinc oxide and nano titanium dioxide in a mass ratio of 0.5-2:0.5-3;

[0008] The lignin / Ni-MOF composite gel is prepared by the following steps:

[0009] Step A1, adding 2,5-dihydroxyterephthalic acid and nickel nitrate hexahydrate to a mixture of DMF, deionized water and ethanol in a volume ratio of 1:1:1 and stirring for 30 minutes, then slowly adding 0.4 mol / L sodium hydroxide solution and stirring for 10-20 minutes, then transferring to an autoclave, and reacting at 120° C. for 6-8 hours, centrifuging, washing and drying to obtain Ni-MOF-OH (nickel-based metal organic framework containing hydroxyl functional groups);

[0010] Step A2, placing Ni-MOF-OH powder in a tube furnace, heating to 700-800°C at a heating rate of 3°C / min under flowing argon, and keeping the temperature for 40-60min, washing to neutrality, and drying to obtain magnetized Ni-MOF;

[0011] Step A3, dispersing lignin in deionized water, slowly adding 30wt% hydrogen peroxide under stirring conditions, adjusting the pH to 5-7, heating to 60-80°C, reacting for 2-3h, centrifuging, washing, and drying to obtain modified lignin;

[0012] Step A4, dispersing calcium chloride in deionized water, recorded as a mixed solution; dispersing the modified lignin in deionized water, adding the magnetized Ni-MOF and stirring for 1-2 hours, then slowly adding the mixed solution, curing for 1 hour, washing, and freeze-drying to obtain a lignin / Ni-MOF composite gel;

[0013] Further, in step A1, the usage ratio of 2,5-dihydroxyterephthalic acid, nickel nitrate hexahydrate, mixed solution and sodium hydroxide solution is 0.4-1.2 g: 0.5-1.5 g: 150 mL: 10 mL;

[0014] Further, in step A3, the mass ratio of lignin, deionized water and hydrogen peroxide is 2-4:10:0.1-0.2;

[0015] Furthermore, in step A4, the usage ratio of modified lignin, deionized water, magnetized Ni-MOF and mixed solution is 1-3 g: 200 mL: 0.5-1.5 g: 100 mL, and the usage ratio of calcium chloride and deionized water in the mixed solution is 1-3 g: 100 mL.

[0016] The modified polyacrylic acid is prepared by the following steps:

[0017] Step B1, dispersing dimethylethylenediamine in N,N-dimethylacetamide, adding triethylamine in an ice-water bath, slowly adding acryloyl chloride and stirring for 30 minutes, then transferring to an oil bath pot, reacting at 55-65° C. for 4-6 hours, then pouring the mixed solution into deionized water at 10° C., filtering, washing and drying to obtain an intermediate product;

[0018] Step B2, dispersing the intermediate product in ethanol, stirring at 45° C., adding 1-chlorododecane dropwise using a constant pressure separatory funnel to react for 8-12 hours, filtering and drying to obtain a functional monomer;

[0019] Step B3, dispersing the emulsifier in deionized water, adding acrylic acid, methyl methacrylate and functional monomers and stirring for 30 minutes to form a pre-emulsion; then adding ammonium persulfate into the deionized water, stirring at 65-75° C. for 20 minutes, then slowly dropping the pre-emulsion and completing the dropping within 1-2 hours, then heating to 80-90° C. and continuing the reaction for 2-3 hours, filtering, and obtaining modified acrylic acid;

[0020] Further, in step B1, the usage ratio of dimethylethylenediamine, acryloyl chloride, triethylamine, N,N-dimethylacetamide and deionized water is 0.1-0.3 mol: 0.11-0.31 mol: 3-7 mL: 100 mL: 200 mL;

[0021] Further, in step B2, the ratio of the intermediate product, ethanol and 1-chlorododecane is 0.1 mol: 100 mL: 0.1 mol;

[0022] Furthermore, in step B3, the mass ratio of ammonium persulfate, deionized water and pre-emulsion is 0.03-0.1:50-80:56-90, and the mass ratio of emulsifier, deionized water, acrylic acid, methyl methacrylate and functional monomer in the pre-emulsion is 1-2:40-60:8-12:5-10:2-6.

[0023] A method for preparing a surfactant for industrial wastewater comprises the following steps:

[0024] The raw materials are weighed in parts by weight, and polyacrylamide, kaolin, activated carbon, lignin / Ni-MOF composite gel, composite photocatalyst and modified polyacrylic acid are stirred and mixed uniformly to obtain a surfactant for industrial wastewater.

[0025] Beneficial effects of the present invention:

[0026] The surfactant prepared by the invention is a composition, which is prepared by stirring and mixing polyacrylamide, kaolin, lignin / Ni-MOF composite gel, composite photocatalyst and modified polyacrylic acid. When the composition is applied to the purification of industrial wastewater, the purification efficiency of the wastewater can be significantly improved. Among them, the lignin / Ni-MOF composite gel has excellent adsorption, flocculation and recyclability; the modified polyacrylic acid achieves the purpose of purification through electrostatic adsorption or chelation; the composite photocatalyst further improves the purification of wastewater by photocatalytic degradation of organic pollutants.

[0027] In the lignin / Ni-MOF composite gel, 2,5-dihydroxyterephthalic acid and nickel nitrate hexahydrate are used as raw materials to synthesize a nickel-based metal organic framework containing hydroxyl groups on the surface; Ni-MOF-OH is then calcined under high temperature and argon conditions to obtain magnetized Ni-MOF; lignin is then oxidized using hydrogen peroxide to obtain modified lignin containing a large number of carboxyl groups and hydroxyl groups; finally, calcium chloride is used as a cross-linking agent to compound the modified lignin containing a large number of carboxyl groups and hydroxyl groups with the magnetized Ni-MOF to prepare the lignin / Ni-MOF composite gel. The three-dimensional network structure and void structure of the lignin / Ni-MOF composite gel can effectively improve the adsorption of pollutants such as heavy metals, organic pollutants, and phosphorus compounds in wastewater by the matrix after it is introduced into the matrix, and at the same time has recycling performance; among them, the modified lignin can use its own active groups, such as hydroxyl and carboxyl groups, to make pollutants such as heavy metal ions in wastewater produce adsorption or flocculation with it, thereby purifying the wastewater; the magnetic Ni-MOF can be better dispersed in the composite gel through the synergistic effect with the carboxyl groups in the modified lignin, increasing the mechanical strength of the gel, making the composite gel easy to form and maintain a stable structure during the application process, and at the same time, the magnetism of Ni-MOF after calcination enables the composite gel to be quickly separated and recovered by magnets during subsequent recycling, thereby improving the recycling performance. In addition, the composite of magnetic Ni-MOF and lignin also increases the specific surface area of ​​the lignin / Ni-MOF composite gel, thereby exposing more active sites, which is conducive to the adsorption of pollutants on its surface, and further improves the purification effect of the matrix on wastewater.

[0028] Modified polyacrylic acid is synthesized with acrylic acid, methyl methacrylate and functional monomer as raw materials, SE-10N as emulsifier and ammonium persulfate as initiator; the introduction of modified polyacrylic acid can form a stable complex with metal cations in wastewater through the carboxyl group in its molecule, thereby reducing the content of metal ions in wastewater; at the same time, the flocculation and adsorption mechanisms of polyacrylic acid work together to make the polar groups of its polymer attract the suspended matter and particulate matter in the water to form an adsorption layer, thereby aggregating the suspended matter to form a larger floc, which can effectively improve the transparency of water and purify wastewater through post-treatment; in addition, the quaternary ammonium salt structure introduced in the modified polyacrylic acid can also generate an electric attraction with the charged impurities in the water through the electric neutralization effect, reduce the concentration of the charged impurities, make them lose stability and aggregate into flocs, thereby removing suspended solids and turbidity in the water, and further improving the purification efficiency of wastewater. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] The lignin / Ni-MOF composite gel was prepared by the following steps:

[0032] Step A1, adding 0.4 g of 2,5-dihydroxyterephthalic acid and 0.5 g of nickel nitrate hexahydrate to a mixture of 50 mL of DMF, 50 mL of deionized water and 50 mL of ethanol, stirring for 30 min, then slowly adding 10 mL of 0.4 mol / L sodium hydroxide solution and stirring for 10 min, then transferring to an autoclave, reacting at 120° C. for 6 h, centrifuging, washing and drying to obtain Ni-MOF-OH;

[0033] Step A2, placing Ni-MOF-OH powder in a tube furnace, heating to 700°C at a heating rate of 3°C / min under flowing argon, and keeping the temperature for 40 minutes, washing to neutrality, and drying to obtain magnetized Ni-MOF;

[0034] Step A3, dispersing 2 g of lignin in 10 g of deionized water, slowly adding 0.1 g of 30 wt% hydrogen peroxide under stirring, adjusting the pH to 5, heating to 60° C., reacting for 2 h, centrifuging, washing, and drying to obtain modified lignin;

[0035] Step A4, disperse 1g of calcium chloride in 100mL of deionized water, record as mixed solution; disperse 1g of modified lignin in 200mL of deionized water, add 0.5g of magnetized Ni-MOF and stir for 1h, then slowly add 100mL of the mixed solution, solidify for 1h, wash and freeze-dry to obtain lignin / Ni-MOF composite gel.

[0036] Modified polyacrylic acid is prepared by the following steps:

[0037] Step B1, dispersing dimethylethylenediamine in N, N-dimethylacetamide, adding triethylamine under ice-water bath conditions, then slowly adding acryloyl chloride and stirring for 30 minutes, then transferring to an oil bath pot, reacting at 55° C. for 4 hours, then pouring the mixed solution into deionized water at 10° C., filtering, washing, and drying to obtain an intermediate product, wherein the amount ratio of dimethylethylenediamine, acryloyl chloride, triethylamine, N, N-dimethylacetamide and deionized water is 0.1 mol: 0.11 mol: 3 mL: 100 mL: 200 mL;

[0038] Step B2, dispersing the intermediate product in ethanol, stirring at 45°C, adding 1-chlorododecane dropwise using a constant pressure separatory funnel for reaction for 8 hours, filtering and drying to obtain a functional monomer, wherein the amount ratio of the intermediate product, ethanol and 1-chlorododecane is 0.1 mol: 100 mL: 0.1 mol;

[0039] Step B3, dispersing the emulsifier SE-10N in deionized water, adding acrylic acid, methyl methacrylate and functional monomers and stirring for 30 minutes to form a pre-emulsion; then adding ammonium persulfate to the deionized water, stirring at 65°C for 20 minutes, slowly dripping the pre-emulsion, and dripping it all within 1 hour, then heating to 80°C and continuing to react for 2 hours, filtering to obtain modified acrylic acid, the mass ratio of ammonium persulfate, deionized water and pre-emulsion is 0.03:50:56, and the mass ratio of emulsifier SE-10N, deionized water, acrylic acid, methyl methacrylate and functional monomers in the pre-emulsion is 1:40:8:5:2.

[0040] Example 2

[0041] The lignin / Ni-MOF composite gel was prepared by the following steps:

[0042] Step A1, 0.8 g of 2,5-dihydroxyterephthalic acid and 1 g of nickel nitrate hexahydrate were added to a mixture of 50 mL of DMF, 50 mL of deionized water and 50 mL of ethanol, and stirred for 30 min, then 10 mL of 0.4 mol / L sodium hydroxide solution was slowly added dropwise and stirred for 15 min, then transferred to an autoclave, and reacted at 120° C. for 7 h, centrifuged, washed and dried to obtain Ni-MOF-OH;

[0043] Step A2, placing Ni-MOF-OH powder in a tube furnace, heating to 750°C at a heating rate of 3°C / min under flowing argon, and keeping the temperature for 50 min, washing to neutrality, and drying to obtain magnetized Ni-MOF;

[0044] Step A3, dispersing 3 g of lignin in 10 g of deionized water, slowly adding 0.15 g of 30 wt% hydrogen peroxide under stirring, adjusting the pH to 6, heating to 70° C., reacting for 2.5 h, centrifuging, washing, and drying to obtain modified lignin;

[0045] Step A4, disperse 2g of calcium chloride in 100mL of deionized water, record as mixed solution; disperse 2g of modified lignin in 200mL of deionized water, add 1g of magnetized Ni-MOF and stir for 1.5h, then slowly add 100mL of the mixed solution, solidify for 1h, wash and freeze-dry to obtain lignin / Ni-MOF composite gel.

[0046] Modified polyacrylic acid is prepared by the following steps:

[0047] Step B1, dispersing dimethylethylenediamine in N, N-dimethylacetamide, adding triethylamine under ice-water bath conditions, then slowly adding acryloyl chloride and stirring for 30 minutes, then transferring to an oil bath pot, reacting at 60°C for 5 hours, then pouring the mixed solution into 10°C deionized water, filtering, washing, and drying to obtain an intermediate product, wherein the amount ratio of dimethylethylenediamine, acryloyl chloride, triethylamine, N, N-dimethylacetamide and deionized water is 0.2 mol: 0.21 mol: 5 mL: 100 mL: 200 mL;

[0048] Step B2, dispersing the intermediate product in ethanol, stirring at 45°C, adding 1-chlorododecane dropwise using a constant pressure separatory funnel to react for 10 hours, filtering and drying to obtain a functional monomer, wherein the amount ratio of the intermediate product, ethanol and 1-chlorododecane is 0.1 mol: 100 mL: 0.1 mol;

[0049] Step B3, dispersing the emulsifier SE-10N in deionized water, adding acrylic acid, methyl methacrylate and functional monomers and stirring for 30 minutes to form a pre-emulsion; then adding ammonium persulfate to the deionized water, stirring at 70°C for 20 minutes, and then slowly dripping the pre-emulsion, and dripping it within 1.5 hours, then heating to 85°C and continuing to react for 2.5 hours, filtering, and obtaining modified acrylic acid, the mass ratio of ammonium persulfate, deionized water and pre-emulsion is 0.07:65:73.5, and the mass ratio of emulsifier SE-10N, deionized water, acrylic acid, methyl methacrylate and functional monomers in the pre-emulsion is 1.5:50:10:8:4.

[0050] Example 3

[0051] The lignin / Ni-MOF composite gel was prepared by the following steps:

[0052] Step A1, adding 1.2 g of 2,5-dihydroxyterephthalic acid and 1.5 g of nickel nitrate hexahydrate to a mixture of 50 mL of DMF, 50 mL of deionized water and 50 mL of ethanol, stirring for 30 min, then slowly adding 10 mL of 0.4 mol / L sodium hydroxide solution and stirring for 20 min, then transferring to an autoclave, reacting at 120° C. for 8 h, centrifuging, washing and drying to obtain Ni-MOF-OH;

[0053] Step A2, placing Ni-MOF-OH powder in a tube furnace, heating to 800°C at a heating rate of 3°C / min under flowing argon, and keeping the temperature for 60 minutes, washing to neutrality, and drying to obtain magnetized Ni-MOF;

[0054] Step A3, dispersing 4 g of lignin in 10 g of deionized water, slowly adding 0.2 g of 30 wt% hydrogen peroxide under stirring, adjusting the pH to 7, heating to 80° C., reacting for 3 h, centrifuging, washing, and drying to obtain modified lignin;

[0055] Step A4, disperse 3g of calcium chloride in 100mL of deionized water, record as mixed solution; disperse 3g of modified lignin in 200mL of deionized water, add 1.5g of magnetized Ni-MOF and stir for 2h, then slowly add 100mL of the mixed solution, solidify for 1h, wash and freeze-dry to obtain lignin / Ni-MOF composite gel.

[0056] Modified polyacrylic acid is prepared by the following steps:

[0057] Step B1, dispersing dimethylethylenediamine in N, N-dimethylacetamide, adding triethylamine under ice-water bath conditions, slowly adding acryloyl chloride and stirring for 30 minutes, then transferring to an oil bath pot, reacting at 65°C for 6 hours, then pouring the mixed solution into deionized water at 10°C, filtering, washing and drying to obtain an intermediate product, wherein the amount ratio of dimethylethylenediamine, acryloyl chloride, triethylamine, N, N-dimethylacetamide and deionized water is 0.3 mol: 0.31 mol: 7 mL: 100 mL: 200 mL;

[0058] Step B2, dispersing the intermediate product in ethanol, stirring at 45°C, adding 1-chlorododecane dropwise using a constant pressure separatory funnel to react for 12 hours, filtering and drying to obtain a functional monomer, wherein the amount ratio of the intermediate product, ethanol and 1-chlorododecane is 0.1 mol: 100 mL: 0.1 mol;

[0059] Step B3, dispersing the emulsifier SE-10N in deionized water, adding acrylic acid, methyl methacrylate and functional monomers and stirring for 30 minutes to form a pre-emulsion; then adding ammonium persulfate to the deionized water, stirring at 75°C for 20 minutes, and then slowly dripping the pre-emulsion, and dripping it within 1-2 hours, and then heating to 80-90°C to continue the reaction for 3 hours, filtering, and obtaining modified acrylic acid, the mass ratio of ammonium persulfate, deionized water and pre-emulsion is 0.1:80:90, and the mass ratio of emulsifier SE-10N, deionized water, acrylic acid, methyl methacrylate and functional monomers in the pre-emulsion is 2:60:12:10:6.

[0060] Example 4

[0061] A method for preparing a surfactant for industrial wastewater comprises the following steps:

[0062] Step S1, mixing nano zinc oxide and nano titanium dioxide at a mass ratio of 0.5:2 to prepare a composite photocatalyst;

[0063] Step S2, weighing raw materials by weight, and stirring and mixing 20 parts of polyacrylamide, 7 parts of kaolin, 3 parts of activated carbon, 5 parts of lignin / Ni-MOF composite gel prepared in Example 1, 3 parts of composite photocatalyst and 3 parts of modified polyacrylic acid prepared in Example 1 to obtain a surfactant for industrial wastewater.

[0064] Example 5

[0065] A method for preparing a surfactant for industrial wastewater comprises the following steps:

[0066] Step S1, mixing nano zinc oxide and nano titanium dioxide at a mass ratio of 1:1.5 to prepare a composite photocatalyst;

[0067] Step S2, weighing raw materials by weight, and stirring and mixing 25 parts of polyacrylamide, 8 parts of kaolin, 5 parts of activated carbon, 9 parts of lignin / Ni-MOF composite gel prepared in Example 2, 5 parts of composite photocatalyst and 4 parts of modified polyacrylic acid prepared in Example 2 to obtain a surfactant for industrial wastewater.

[0068] Example 6

[0069] A method for preparing a surfactant for industrial wastewater comprises the following steps:

[0070] Step S1, mixing nano zinc oxide and nano titanium dioxide in a mass ratio of 2:1 to prepare a composite photocatalyst;

[0071] Step S2, weighing raw materials by weight, and stirring and mixing 30 parts of polyacrylamide, 10 parts of kaolin, 6 parts of activated carbon, 12 parts of lignin / Ni-MOF composite gel prepared in Example 3, 6 parts of composite photocatalyst and 5 parts of modified polyacrylic acid prepared in Example 3 to obtain a surfactant for industrial wastewater.

[0072] Comparative Example 1

[0073] This comparative example is a surfactant, which is different from Example 6 in that the lignin / Ni-MOF composite gel prepared in Example 3 is replaced by silica aerogel, and the rest is the same.

[0074] Comparative Example 2

[0075] This comparative example is a surfactant, which is different from Example 6 in that polyacrylic acid is used instead of the modified polyacrylic acid prepared in Example 3, and the rest is the same.

[0076] The surfactants prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests: they were added to industrial wastewater, the ratio of surfactant to wastewater was 10 g: 1 L, treated for 3 h under sunlight and a rotation speed of 150 rpm, left to stand for 30 min, and the upper layer of liquid was taken. The removal rates (%) of phosphorus, COD, formaldehyde, heavy metals, and other harmful particulate matter in the wastewater before and after treatment were tested in accordance with CJ / T 51-2018 "Standard Test Methods for Urban Sewage Quality". The test results are shown in the following table:

[0077]

[0078]

[0079] As can be seen from the above table, the surfactant in this application has a COD removal rate of 89.3%-91.1% for industrial wastewater, a toluene removal rate of 91.7%-94.1%, a phosphorus-containing compound removal rate of 90.4%-92.5%, a heavy metal ion removal rate of 86.1%-87.6%, and a removal rate of other harmful particulate matter of 89.6%-92.6%, indicating that the addition of the surfactant can effectively purify industrial wastewater and remove pollutants in the wastewater.

[0080] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A surfactant for industrial wastewater, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of polyacrylamide, 7-10 parts of kaolin, 3-6 parts of activated carbon, 5-12 parts of lignin / Ni-MOF composite gel, 3-6 parts of composite photocatalyst, and 3-5 parts of modified polyacrylic acid; The lignin / Ni-MOF composite gel is prepared by the following steps: Step A1, adding 2,5-dihydroxyterephthalic acid and nickel nitrate hexahydrate to a mixture of DMF, deionized water and ethanol in a volume ratio of 1:1:1, stirring for 30 minutes, then slowly adding 0.4 mol / L sodium hydroxide solution and stirring for 10-20 minutes, then transferring to an autoclave, reacting at 120°C for 6-8 hours, centrifuging, washing and drying to obtain Ni-MOF-OH; Step A2, placing Ni-MOF-OH powder in a tube furnace, heating to 700-800°C at a heating rate of 3°C / min under flowing argon, and keeping the temperature for 40-60min, washing to neutrality, and drying to obtain magnetized Ni-MOF; Step A3, dispersing lignin in deionized water, slowly adding 30wt% hydrogen peroxide under stirring conditions, adjusting the pH to 5-7, heating to 60-80°C, reacting for 2-3h, centrifuging, washing, and drying to obtain modified lignin; Step A4, dispersing calcium chloride in deionized water, recorded as a mixed solution; dispersing the modified lignin in deionized water, adding the magnetized Ni-MOF and stirring for 1-2 hours, then slowly adding the mixed solution, curing for 1 hour, washing, and freeze-drying to obtain a lignin / Ni-MOF composite gel.

2. A surfactant for industrial wastewater according to claim 1, characterized in that: In step A1, the usage ratio of 2,5-dihydroxyterephthalic acid, nickel nitrate hexahydrate, mixed solution and sodium hydroxide solution is 0.4-1.2 g: 0.5-1.5 g: 150 mL: 10 mL.

3. A surfactant for industrial wastewater according to claim 1, characterized in that: In step A3, the mass ratio of lignin, deionized water and hydrogen peroxide is 2-4:10:0.1-0.

2.

4. The surfactant for industrial wastewater according to claim 1, characterized in that: In step A4, the usage ratio of modified lignin, deionized water, magnetized Ni-MOF and mixed solution is 1-3 g: 200 mL: 0.5-1.5 g: 100 mL, and the usage ratio of calcium chloride and deionized water in the mixed solution is 1-3 g: 100 mL.

5. The surfactant for industrial wastewater according to claim 1, characterized in that: The composite photocatalyst is prepared by mixing nano zinc oxide and nano titanium dioxide in a mass ratio of 0.5-2:0.5-3.

6. The surfactant for industrial wastewater according to claim 1, characterized in that: The modified polyacrylic acid is prepared by the following steps: Step B1, dispersing dimethylethylenediamine in N,N-dimethylacetamide, adding triethylamine in an ice-water bath, slowly adding acryloyl chloride and stirring for 30 minutes, then transferring to an oil bath pot, reacting at 55-65° C. for 4-6 hours, then pouring the mixed solution into deionized water at 10° C., filtering, washing and drying to obtain an intermediate product; Step B2, dispersing the intermediate product in ethanol, stirring at 45° C., adding 1-chlorododecane dropwise using a constant pressure separatory funnel to react for 8-12 hours, filtering and drying to obtain a functional monomer; Step B3, dispersing the emulsifier in deionized water, adding acrylic acid, methyl methacrylate and functional monomer and stirring for 30 minutes to form a pre-emulsion; Then add ammonium persulfate into deionized water, stir at 65-75°C for 20 minutes, slowly add the pre-emulsion and finish adding it within 1-2 hours, then heat to 80-90°C and continue to react for 2-3 hours, filter, and obtain modified acrylic acid.

7. A surfactant for industrial wastewater according to claim 6, characterized in that: In step B1, the usage ratio of dimethylethylenediamine, acryloyl chloride, triethylamine, N,N-dimethylacetamide and deionized water is 0.1-0.3 mol: 0.11-0.31 mol: 3-7 mL: 100 mL: 200 mL.

8. A surfactant for industrial wastewater according to claim 6, characterized in that: In step B2, the usage ratio of the intermediate product, ethanol and 1-chlorododecane is 0.1 mol:100 mL:0.1 mol.

9. The surfactant for industrial wastewater according to claim 6, characterized in that: In step B3, the mass ratio of ammonium persulfate, deionized water and pre-emulsion is 0.03-0.1:50-80:56-90, and the mass ratio of emulsifier, deionized water, acrylic acid, methyl methacrylate and functional monomer in the pre-emulsion is 1-2:40-60:8-12:5-10:2-6.

10. The method for preparing a surfactant for industrial wastewater according to claim 1, characterized in that: The following steps are involved: The raw materials are weighed in parts by weight, and polyacrylamide, kaolin, activated carbon, lignin / Ni-MOF composite gel, composite photocatalyst and modified polyacrylic acid are stirred and mixed uniformly to obtain a surfactant for industrial wastewater.

Citation Information

Patent Citations

  • Three-dimensional fiber-based aerogel tissue engineering scaffold and preparation method thereof

    CN103285424A

  • Natural polymer-based composite solid electrolyte as well as preparation method and application thereof

    CN115642304A